MICAL-L2 Is Essential for c-Myc Deubiquitination and Stability in Non-small Cell Lung Cancer Cells - Min, Pengxiang; Zhang, Lin; Wang, Yueyuan; Qi, Chenxiang; Song, Yixuan; Bibi, Maria; Zhang, Yujie; Ma, Yadong; Zhao, Xuyang; Yu, Minjie; Du, Jun (Frontiers in Cell and Developmental Biology, 2021)
Objectives: MICAL-L2, a member of the molecules interacting with the CasL (MICAL) family, was reported to be highly expressed in several types of cancers, however, the roles of MICAL-L2 in NSCLC pathogenesis remain to be explored. This study is designed to clarify the mechanisms by which MICAL-L2 participates in NSCLC cell proliferation. Materials and Methods: The expression levels of MICAL-L2 in human lung cancer samples were assessed by immunohistochemical staining. Cells were transfected with siRNA or plasmids to regulate MICAL-L2 expression. Cell proliferation was measured by EdU staining and CCK-8 assays. MICAL-L2 and phosphorylated/total c-Myc expression were examined by Western blotting analysis. Interaction between MICAL-L2 and c-Myc was assessed by immunofluorescence staining, Western blotting and co-immunoprecipitation assays. Western blotting, polyubiquitylation detection and protein stability assays were used to assess whether MICAL-L2 exerts its oncogenic effect via c-Myc. Results: We found that MICAL-L2 was highly expressed in human NSCLC. While overexpressing MICAL-L2 increased NSCLC cell proliferation, MICAL-L2 depletion decreased the proliferation of NSCLC cells, an effect that was linked to cell cycle arrest. MICAL-L2 physically interacted with the c-Myc protein and functioned to maintain nuclear c-Myc levels and prolonged its half-life. Knockdown of MICAL-L2 expression led to decreased c-Myc protein stability through accelerating polyubiquitylation of c-Myc and gave rise to c-Myc degradation. We further found that MICAL-L2 deubiquitinated c-Myc and blocked its degradation, presumably by inhibiting c-Myc phosphorylation at threonine residue 58. Conclusions: These results indicate that MICAL-L2 is a key regulator of c-Myc deubiquitination and stability in the nucleus, and this activity may be involved in promoting NSCLC cell proliferation.